A case of adrenal cortical carcinoma with inferior vena cava thrombus extending into the right atrium: a two staged procedure - Magesh, Chandranathan; Thangarasu, Mathisekaran; JayaPrakash, SanjayPrakash; Jain, Nitesh (International Surgery Journal, 2020)
We present a case of adrenal cortical carcinoma (ACC) with tumor thrombus involving the inferior vena cava (IVC) and right atrium in a morbidly obese, middle-aged female. ACC is a rare type of cancer with a poor outcome. Most cases present with metastasis at the time of initial presentation. This patient presented with breathing difficulty and flank pain. With endocrinology evaluation and collaborative effort of multidisciplinary teams, the patient successfully underwent staged procedures of atrial clot evacuation after thoracotomy with cardiopulmonary bypass (CBP) along with inferior vena cava thrombectomy (IVCT) and left radical nephroadrenalectomy. The two staged procedure reduces the mortality when compared with a single staged procedure. The patient underwent atrial clot evacuation, performed by cardiothoracic surgery team under CBP and deployment of IVC filter by interventional radiologist as a first staged procedure. At six months of follow-up, the patient had locoregional disease spread but with good functional status. This case report highlights that even a high-volume disease, with proper planning by an experienced surgical team, can be operated successfully with an acceptable post-surgery quality of life for the patients.